1997
DOI: 10.1051/rnd:19970509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arginine, growth hormone-releasing hormone (GHRH) and neostigmine administered singly or in paired combinations on growth hormone (GH) release in pigs

Abstract: Summary -In human, arginine (ARG) induces growth hormone (GH) release, probably via a decrease in somatostatinergic tone. To assess the mechanism by which ARG mediates GH release in pigs, the effects on plasma GH release of ARG ( 1 g/kg body weight, infused between times -15 and -5 min), growth hormone-releasing hormone (GHRH, 2 pg/kg, at time 0 min) and neostigmine, a cholinesterase inhibitor (NEO, 50 arginine / growth hormone-releasing hormone / néostigmine / hormone de croissance / porc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…() reported that GLP‐2 exerted positive effects on the FI and BWG of chickens, small intestinal weight and mucosal growth, the digestive and absorptive functions of the GIT. Similarly, in this study, IOF of Arg increased the concentration of intestinal GLP‐2 and VIP, which was closely related to the secretagogue activity of Arg or its product NO (Cochard, Guilhermet, & Bonneau, ). It is well established that Arg has a secretagogue activity by which it stimulates the release of pituitary and gastrointestinal hormones, including glucagon, insulin, ghrelin and growth hormone.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…() reported that GLP‐2 exerted positive effects on the FI and BWG of chickens, small intestinal weight and mucosal growth, the digestive and absorptive functions of the GIT. Similarly, in this study, IOF of Arg increased the concentration of intestinal GLP‐2 and VIP, which was closely related to the secretagogue activity of Arg or its product NO (Cochard, Guilhermet, & Bonneau, ). It is well established that Arg has a secretagogue activity by which it stimulates the release of pituitary and gastrointestinal hormones, including glucagon, insulin, ghrelin and growth hormone.…”
Section: Discussionsupporting
confidence: 73%
“…It is well established that Arg has a secretagogue activity by which it stimulates the release of pituitary and gastrointestinal hormones, including glucagon, insulin, ghrelin and growth hormone. This induced‐hormone production can increase protein synthesis and intestinal enzyme activities, which further increase the FI and subsequent the BWG of post‐hatch broilers (Cochard et al., ; Lotfi, Shahryar, & Kaiya, ).…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al (2018) reported that Arg increased the concentration of growth hormone in broiler chickens. Similarly, Cochard et al (1997) reported a significant increase in growth hormone when Arg was injected into jugular vein of 35-d-old piglets. The reasons for the lack of difference in serum growth hormone concentration among treatments in the present study (P > 0.05) are unknown.…”
Section: Resultsmentioning
confidence: 83%
“…This is believed to be due to their somatostatinergic hypertone [35]. ARG-induced GH release is probably mediated by a decrease in the somatostatinergic tone as demonstrated indirectly by the use of cholinesterase inhibitors in man [1,18,20] and pigs [10].…”
mentioning
confidence: 99%